Konsep Moderasi Islam dalam Pemikiran - Nur, Muhammad (Universitas Muhammadiyah Surabaya, 2024)
Currently, the Islamic Moderation discourse has become an alternative Islamic thought that is very important in the lives of Muslims. Islamic moderation, which is part of a form of Islamic thought that is original to Islamic teachings, is expected to bring about a better, fairer, superior and civilized life for Muslims. Islamic moderation or wasathiyah is the main characteristic of Islam taught by Allah in the Qur'an and also in the Sunnah. That this people is a moderate and middle-class people that Allah has orbited among humans. Therefore, the aim of this study is to exploit and socialize moderate Islamic teachings to Indonesian society and the world, so that Islam becomes a religion that is a blessing for all nature. The writing method in this study uses library methods and classical and contemporary Islamic literacy approaches. From here it is then analyzed according to the context of Muslim life in Indonesia, especially in aspects of Islamic thought that developed in Indonesia. Results of this study. First: To give birth to the concept of moderate Islamic thought towards a moderate understanding and attitude in implementing Islam in accordance with the Al-Qur'an and As-Sunnah. Second: provide a clear distinction between moderate thought and other Islamic thought. Keywords: Moderation, thought, Islam, contemporary